Genetic engineering of bacteria for the production of antibiotics: A review - Tehseen Zafar; Taswar Ahsan; Wu Yuanhua (Future Science, 2023)
Due to high demand of antibiotics for treatment of increasing bacterial infections there is an urgent need of engineering bacterial strains to get high concentration and meet industrial demands. Different techniques are being used for this purpose: which include over-expression of a gene in its host strain, engineering of different activators and regulators of antibiotic synthesizing gene cluster and expression of antibiotic gene cluster in heterologous host. The emergence of antibiotic resistant pathogens was a huge problem for existing medications and it urges a need or the development of novel antibiotics with high specificity. These can be produced by combinatorial biosynthesis or awakening of silent genes already present in bacteria. These advancements present a bright future of antibiotic production at industrial level.